Pengaruh Pendidikan dan Pelatihan (Diklat) dan Motivasi Kerja Terhadap Kinerja Pegawai Pada RSUD Pandega Pangandaran - Yeti Kusmiati; Apri Budianto; Aini Kusniawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Employee performance is not optimal, this can be seen from the level of punctuality which gets the lowest score. Based on the results of an interview with the head of the civil service section at Pandega Pangandaran Regional Hospital, punctuality has decreased because there are still employees coming and going home not according to the specified schedule. The level of quality (quality) is not yet optimal, this is because employees are not doing their work on time according to the predetermined targets. Employee performance is influenced by training and work motivation. Overall, it can be concluded that the training at Pandega Hospital, Pangandaran Regency has not been fully effective. Employee responses to the implementation of training education in 2023 show that there is a lack of achievement. This is because the training materials and techniques are not appropriate to the objectives and cannot be understood by participants. Overall motivation at Pandega Hospital, Pangandaran Regency can be said to be mediocre. This can be seen from the employee's response to the existence indicator which is the lowest indicator. The monthly salary provided is not enough to meet the daily needs of employees, while the health insurance offered by the company functions as a motivating factor for employees. This research uses a descriptive and case study approach, with a quantitative design. The data analysis techniques used include testing instruments to assess validity and reliability, testing research models using the coefficient of determination, and testing hypotheses through t tests and F tests. The results of the research show that (1) Training has a positive and significant effect on employee performance at RSUD Pandega Pangandaran. This means that if training is improved, the performance of employees at Pandega Pangandaran Regional Hospital will also increase. (2) Work motivation has a positive and significant effect on employee performance at Pandega Pangandaran Regional Hospital. This means that if work motivation is increased, the performance of employees at Pandega Pangandaran Regional Hospital will also increase. (3) Training and work motivation have a positive and significant effect on employee performance at Pandega Pangandaran Regional Hospital. This means that if training and work motivation are improved, the performance of employees at Pandega Pangandaran Regional Hospital will also increase.